Association Of Neuropathic Pain Improvement And hs-CRP Changes Among Trigeminal Neuralgia Patients Experienced Radiofrequency Ablation 60o and 65o Celcius: 6 months follow up - Arlina, Yani; Budisulistyo, Trianggoro; Pudjonarko, Dwi; Tugasworo, Dodik; Suryawati, Herlina; Diah Pasmanasari, Elta (RSUP Dr. Kariadi, 2023)
INTRODUCTION: Trigeminal neuralgia (NT) is a neuropathic pain that involves the trigeminal nerve in the face. The first-line medical management of patients with NT is Carbamazepine (CBZ). Radiofrequency ablation (RFA) procedure is a minimally invasive procedure using a high-frequency current-generating device that produced heat ablate of C-fibers with effectiveness around 76% for 10 yeas follow-up. Inflammed trigeminal nerve (TG) or the branch(es) might be one of the underlying mechanisms unless vascular compression is a common etiology. The heat effects might be according to the temperature set up varies recently from 60°C to 95°C. METHOD: This observational study enrolled 75 severe NT subjects without satisfactory improvement of treatments, divided into 3 groups: analgesics prescription (Control), RFA 60, and RFA 65 Groups. The LANSS scores and hs-CRP levels were followed-up before (baseline), 2 weeks, 3, and 6 months experienced the treatments. Subjects ages in the range of 48.32 + 12.73 to 50.88 + 14.59 years old, and the duration of illness from 4.48 to 10.32 months. RESULT: The LANSS score >12 before treatments showed significance improvements (p<0.001), as in the Control (64% with neuropathic pain), RFA 60 (100% with neuropathic pain), and RFA 65 group (92% with nociceptive pain) at 2 weeks followed-up. At 3 and 6 months observed 100% subjects with nociceptive pain but without significancies. Even though the hs-CRP levels observed reduced for all groups, especially RFA 60 and RFA 65, but have no significances. CONCLUSION: The LANSS scores changes observed significant improvement in all groups, which mentioned if the neuropathic pain syndromes might be better under each treatment. The Hs-CRP levels improvement is better in the neuro ablation groups than analgesic drugs treatment. Even though the Hs-CRP are following of systemic nonspecific inflammation, NT is a focal inflammation.